2020
DOI: 10.1136/annrheumdis-2019-216274
|View full text |Cite|
|
Sign up to set email alerts
|

Initial combination therapy of ambrisentan and tadalafil in connective tissue disease-associated pulmonary arterial hypertension (CTD-PAH) in the modified intention-to-treat population of the AMBITION study: post hoc analysis

Abstract: ObjectivesTo evaluate initial combination therapy with ambrisentan plus tadalafil (COMB) compared with monotherapy of either agent (MONO), and the utility of baseline characteristics and risk stratification in predicting outcomes, in patients with connective tissue disease-associated pulmonary arterial hypertension (CTD-PAH) and the systemic sclerosis (SSc)–pulmonary arterial hypertension (PAH) subpopulation.MethodsThis post hoc analysis of the Ambrisentan and Tadalafil in Patients with Pulmonary Arterial Hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 33 publications
1
29
1
1
Order By: Relevance
“…The combination was well tolerated and considered safe. These data confirm recently revised treatment guidelines, suggesting that initial combined therapy for newly diagnosed patients, even when symptoms are mild, may be of value to clinicians [ 49 ].…”
Section: Resultssupporting
confidence: 83%
“…The combination was well tolerated and considered safe. These data confirm recently revised treatment guidelines, suggesting that initial combined therapy for newly diagnosed patients, even when symptoms are mild, may be of value to clinicians [ 49 ].…”
Section: Resultssupporting
confidence: 83%
“…37 Several studies have reported the efficacy of up-front combination therapy to target 2 pathways simultaneously, thereby improving the clinical outcome of PH: death, hospitalization, and symptoms. 38,39 Furthermore, our study showed that early stabilization of PH hemodynamics could lower the incidence of CKD progression presumably through the improvement of cardiac output and renal perfusion. Another mechanism for the prominent effect on CKD progression of pulmonary vasodilator combination is their direct renoprotective effect.…”
Section: Discussionmentioning
confidence: 65%
“…In the recently published post hoc analysis of the modified intention to treat CTD-PAH patients included in the AMBITION study [ 8 ], an abbreviated version of the SPAHR/COMPERA risk assessment [ 19 , 20 ] based on three criteria (WHO-FC, NTproBNP and 6MWT), as well as the low-risk noninvasive criteria model used by the French registry [ 18 ] were applied. The authors concluded that these abbreviated versions may be useful in predicting PAH-related outcomes in patients with CTD-PAH, but that further research, including large patient cohorts for identifying the most optimal predictive tools, is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…PAH is a serious complication in CTD and is associated with a highly unfavourable prognosis [3][4][5][6]. Despite improvement of functional parameters and survival rate by modern treatment, [7,8] the outcome of patients with CTD-PAH, and especially of those with systemic sclerosis associated PAH (SSc-PAH), remains poor [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation